The Correlation of Asthma Patients' Knowledge Level With Asthma Symptoms Control Level - Mardhiah (Caring: Indonesian Journal of Nursing Science, 2021)
Asthma is a disease caused by disorders in the respiratory tract due to allergies or genetics. It cannot be cured, but it can be controlled. With medical treatment and proper self-management, asthma patients can achieve a good asthma symptoms control level. One of the factors affecting asthma control is knowledge about asthma. This study aims to determine the correlation between knowledge of asthma and asthma symptoms control level at Medan Pulmonology Hospital. This research uses a descriptive correlation research design. Seventy-three respondents were selected using a simple random sampling technique. They are the asthma patients in the Technical Implementation Unit (UPT) of Medan Pulmonology Hospital. This research also used questionnaires of knowledge and asthma symptoms control; then, the results were analyzed. The study results indicated that most asthmatic patients were categorized as having less level knowledge of asthma with 38 respondents (52.1%). In addition, most asthma patients have uncontrolled asthma type with 37 respondents (50.7%). This shows that there is a correlation between level knowledge of asthma and asthma symptoms control level with p = 0.034. Furthermore, Nurses can use this study to provide nursing care and control asthma symptoms to asthmatic patients.